2015
DOI: 10.1002/14651858.cd011054.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral contraceptives: the risk of myocardial infarction and ischemic stroke

Abstract: This meta-analysis showed that the risk of myocardial infarction or ischemic stroke was 1.6-fold increased in women using COCs . The risk was highest for pills with > 50 microgram estrogen. When combined with the results of studies on the risk of venous thrombosis in COC users, it seems that the COC pill containing levonorgestrel and 30 μg of estrogen is the safest oral form of hormonal contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 143 publications
2
143
0
8
Order By: Relevance
“…COC use increases the risk for venous thromboembolism (VTE) by two to four times (21) and for stroke by 1.5 to two times, compared with risk levels in nonusers (22). The risk for VTE or stroke is not statistically different between pills containing 20 mcg and 30 mcg of EE (22,23).…”
Section: Hormonal Contraceptives Thromboembolic Events and Strokementioning
confidence: 99%
“…COC use increases the risk for venous thromboembolism (VTE) by two to four times (21) and for stroke by 1.5 to two times, compared with risk levels in nonusers (22). The risk for VTE or stroke is not statistically different between pills containing 20 mcg and 30 mcg of EE (22,23).…”
Section: Hormonal Contraceptives Thromboembolic Events and Strokementioning
confidence: 99%
“…65 CHCs have been associated with an increased risk of arterial thrombosis but the magnitude of the risk and the effect of different hormonal contents remain unclear. 66,67 The European Medicines Agency (EMA) and the Italian Pharmaceutical Agency (Agenzia Italiana del Farmaco -AIFA) have concluded that the benefits of CHCs in preventing unwanted pregnancies continue to outweigh their risks, and that the wellknown risk of VTE with all CHCs is small. It is important that women are made aware of the risk of VTE and its signs and symptoms, and that doctors take into consideration a woman's individual risk factors when prescribing a contraceptive.…”
Section: Venous Thromboembolism and Combined Hormonal Contraceptive: mentioning
confidence: 99%
“…The important reason for reduction of the estrogen dose in COCs is based on the evidence that COCs are accountable for the development of a hyperclottable state. 23 A recent Cochrane review conducted that preparations containing lower doses of estrogen did not increase the arterial thrombotic risk, and the risk did not vary according to which progestogen type was used.…”
Section: Effect On Haemostasismentioning
confidence: 99%